Effects of swirl at intake manifold on engine performance using ethanol fuel blend - Beny, Cahyono (2015)
Ethanol fuel is widely used as an alternative fuel for gasoline engines. The use of ethanol can reduce dependence on fuel from the fraction of hydrocarbons. The use of ethanol as fuel, however, causes increased fuel consumption. This increase is a result of the low calorific value and a shorter carbon chain. It also raises the value of Reid's vapor, making it difficult to mix with air. Adding swirl generators to the intake manifold aims to make the interior airflow more turbulent. The mixture of fuel with air will also improve. Given these drawbacks, the study analyses the effect of adding a swirl generator to the intake manifold on engine performance, fuel consumption, and emissions produced. The experimentis done on a port injection gasoline engine, four-stroke, SOHC four cylinder connected to the engine dynamometer, which is used to measure the power and emissions produced. To get a good form of swirl generator, experiments were performed using a flow bench. A method has also been developed simultaneously to quantify the swirl characteristics of a swirl generator under steady flow conditions in a flow laboratory using the cylinder head, intake manifold, and swirl generator from the engine experiments. A refined swirl meter is installed under the cylinder head to measure the compressive load of the swirl, allowing for the calculation of angular momentum of the incoming air at varying intake valve lifts, thus producing the swirl number. A correlation is then sought between the engine and flow experiments to help quantify the impact of swirl motion on combustion and cyclic variation. The airflow rate into the cylinder, discharge coefficient of the intake system, and flow loss coefficient across the blockage arealso analyzed for different levels of swirl motion. The validity of this method under steady flow condition is confirmed by comparison of the results with the engine experiments. An engine using ethanol blend fuel has higher fuel consumption, E10 fuel consumption average increase is 12%, and E20 fuel consumption increase is 14%. Increasing the ethanol content further in fuels however will reduce the emissions productions. Performance in relation to the torque, E10 in the case Half Open Throttle at 2000 rpm reduces the engine torque by 3.8 %, at 4000 rpm the engine torque is reduced by 1.6%. E10 in the case of Wide Open Throttle at 2000 rpm reduce the engine torque by 3.4%, and at 4000 rpm reduces the torque by 1.2%. In the case of E20 at Half Open Throttleand rpm 2000 the engine torque reduces by 5.8%, and at 4000 rpm increases by 2.7%. The addition of a swirl generator will increase the engine performance in the case of E20 at Half Open Throttle. The average engine torque increases from 10 until 13 %, in the case of Wide Open Throttle the engine torque increases by 9%. In the case of E10 with Half Open Throttle the engine torque increases by 9%, and with Wide Open Throttle increases by 8,5%. But the emissions generated will be higher in the case of HC at Wide Open Throttle, increasing by 50%.